2011
DOI: 10.1038/jhg.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Screening of genetic variations of SLC15A2, SLC22A1, SLC22A2 and SLC22A6 genes

Abstract: A growing list of membrane-spanning proteins involved in the transport of a large variety of drugs has been recognized and characterized to include peptide and organic anion/cation transporters. Given such an important role of transporter genes in drug disposition process, the role of single-nucleotide polymorphisms (SNPs) in such transporters as potential determinants of interindividual variability in drug disposition and pharmacological response has been investigated. To define the distribution of transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…adenovir, cidofovir, and tenofovir), which suggests a potential for adverse drug reactions in response to antiviral drugs in these patients (Fujita et al, 2005;Xu et al, 2005). Furthermore, Cheong et al (2011), using linkage disequilibrium analyses, identified a haplotype block containing this hOAT1 SNP in an Asian study cohort including Korean, Han Chinese, and Japanese populations, but not in African American or European American cohorts. K525I-hOAT1 mutation was also investigated for altered affinity toward these nucleoside phosphonate analogs, but this mutant seemed to have transport properties similar to those observed in wild type (Bleasby et al, 2005).…”
Section: Population Variability Of Coding Region Polymorphisms In Hummentioning
confidence: 98%
“…adenovir, cidofovir, and tenofovir), which suggests a potential for adverse drug reactions in response to antiviral drugs in these patients (Fujita et al, 2005;Xu et al, 2005). Furthermore, Cheong et al (2011), using linkage disequilibrium analyses, identified a haplotype block containing this hOAT1 SNP in an Asian study cohort including Korean, Han Chinese, and Japanese populations, but not in African American or European American cohorts. K525I-hOAT1 mutation was also investigated for altered affinity toward these nucleoside phosphonate analogs, but this mutant seemed to have transport properties similar to those observed in wild type (Bleasby et al, 2005).…”
Section: Population Variability Of Coding Region Polymorphisms In Hummentioning
confidence: 98%
“…Similarly, in a study of five ethnic groups (n = 450), the minor allele was not detected in any European American, Korean, Han Chinese, or Japanese individuals, and at a frequency of 0.06 among African Americans. 58 Drug disposition depends upon extensive interplay among multiple transporters as well as metabolic enzymes. A greater understanding of this interplay is starting to be unlocked for some drugs, including statins.…”
Section: Findings In Contextmentioning
confidence: 99%
“…There are two main variants of PEPT2 that differ in three amino acid positions, PEPT2*1 (containing amino acids L350, P409, and R509) and PEPT2*2 (containing amino acids F350, S409, and K509) 28 , 30 , 31 . PEPT2*1 is evenly distributed among Caucasians and Africans, while PEPT2*2 exists at higher frequencies in Asians 31 , 32 . Compared with the data from the HapMap database, the frequencies of rs2257212 (L350F), rs1143671 (P409S) and rs1143672 (R509K) were higher in the present study, with values of 47.8%, 55.2% and 52.2%, respectively (Table 5 ).…”
Section: Discussionmentioning
confidence: 92%